PKM WORKSHOP MODEL PEMBELAJARAN INOVATIF DAN KREATIF PADA GURU DI MTS DARUSSALAM RAJA AMPAT - Anwar, Zakiyah; Fahrizal, Ahmad; Budiarti, Marlinda I.E (MATAPPA: Jurnal Pengabdian Kepada Masyarakat, 2020)
The purpose of this activity is Training and introduce to teachers in remote and outermost areas about Learning Models in the classroom in Madrasah Tsanawiyah (MTs) Darussalam Lilinta village. The method used in this activity is lecture and demonstration method. The lecture method is carried out as an effort to improve teacher understanding with an explanation of the stages of each learning model in the classroom while the demonstration method is an effort of elaborating theory in developing models systematically and increasing teacher understanding in applying theory in class. This activity has a positive impact on teachers and the community in the lilinta villages that are remote and outermost and far from urban access. the results of this activity in the form of excellent teacher responses compiled in the form of written reports for each group. In general the impact of this activity is very positive and responsive, this can be seen from the number of teachers who are active in workshop activities